Understanding Tax Compliance in the Informal Sector in a Developing or Emergent Economy a Case Study of Nyarugenge District Rwanda (Global Journal of Management and Business Research, 2021)
Abstract not found
Keywords: Informal sector; tax compliance; developing countries; principles